Hot melt extrusion as an approach to improve solubility, permeability and oral absorption of a psychoactive natural product, piperine. (10th June 2016) - Ashour, Eman A; Majumdar, Soumyajit; Alsheteli, Abdulla; Alshehri, Sultan; Alsulays, Bader; Feng, Xin; Gryczke, Andreas; Kolter, Karl; Langley, Nigel; Repka, Michael A
Abstract: Objective: The aims of the current research project were to investigate the efficiency of various polymers to enhance the solubility and increase the systemic absorption of piperine using hot melt extrusion technology. Methods: Piperine 10–40% w/w and Eudragit® EPO/Kollidon® VA 64 or Soluplus® were mixed, and the resulting blends were extruded using a twin-screw extruder (Process 11, Thermo Fisher Scientific). Drug release profiles and piperine solubility studies of the extrudates were evaluated. A non-everted intestinal sac was employed for the most promising formulation, 10% w/w piperine/Soluplus®, and pure piperine to study the permeability characteristics. Key Findings: Dissolution studies demonstrated enhancement in piperine per cent release of 10% and 20% w/w piperine/Soluplus® extrudates up to 95% and 74%, respectively. The solubility of 10% and 20% piperine/Soluplus® increased more than 160- and 45-fold in water, respectively. Furthermore, permeability studies demonstrated the enhancement in piperine absorption of 10% w/w piperine/Soluplus® extrudates up to 158.9 μg/5 ml compared with pure piperine at 1.3 μg/5 ml within 20 min. Conclusion: These results demonstrated that increasing the bioavailability of piperine may be achieved as demonstrated by findings in this study.